1989
DOI: 10.1139/b89-088
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of cucumber mosaic virus in resistant and susceptible plants of pepper

Abstract: Immunofluorescence microscopy, azur A staining of viral inclusion bodies, and ELISA tests revealed differences between resistant and susceptible decapitated plants of pepper for virus distribution through the plant but not for virus multiplication and spread in the artificially inoculated leaves. Within 7 to 10 days after inoculation, viral antigens were detected with ELISA tests in all organs of the susceptible plants; only in inoculated leaves of highly resistant plants; and in inoculated leaves, primary ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
1
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 10 publications
8
37
1
4
Order By: Relevance
“…A similar type of resistance was described for CMV whereby virus remained localized to the lower portions of the plant (54,156). Dufour et al (54) showed that CMV accumulated in external but not internal phloem in the petiole of the inoculated leaf and the lower stem of the resistant genotype. Derrick & Barker (44) evaluated potato lines resistant to Potato leafroll virus (PLRV) and showed that the resistance was associated with an exclusion of virus from external phloem bundles, whereas virus occurred in both internal and external phloem in the susceptible line.…”
Section: Resistance To Long-distance Movementmentioning
confidence: 67%
See 1 more Smart Citation
“…A similar type of resistance was described for CMV whereby virus remained localized to the lower portions of the plant (54,156). Dufour et al (54) showed that CMV accumulated in external but not internal phloem in the petiole of the inoculated leaf and the lower stem of the resistant genotype. Derrick & Barker (44) evaluated potato lines resistant to Potato leafroll virus (PLRV) and showed that the resistance was associated with an exclusion of virus from external phloem bundles, whereas virus occurred in both internal and external phloem in the susceptible line.…”
Section: Resistance To Long-distance Movementmentioning
confidence: 67%
“…Infection by a second virus, CMV, alleviated this restriction, which suggests that CMV was able to compensate for the defect in the host, either by providing a factor that facilitates movement of both viruses or alleviating the restriction by an unknown mechanism (151,228). A similar type of resistance was described for CMV whereby virus remained localized to the lower portions of the plant (54,156). Dufour et al (54) showed that CMV accumulated in external but not internal phloem in the petiole of the inoculated leaf and the lower stem of the resistant genotype.…”
Section: Resistance To Long-distance Movementmentioning
confidence: 74%
“…New sources of polygenic resistance were obtained and included into breeding programs . To un- (Dufour et al ., 1989) . …”
Section: Introductionmentioning
confidence: 99%
“…Overall, CMV had a strong synergistic effect on symptom development and yield when combined with the other two viruses. These results suggest that CMV-resistant cultivars (Dufour et al 1989;Caranta et al 2004) are beneficial even though they do not possess PepMoV or PMMoV resistance, through the prevention of a synergistic effect of CMV.…”
Section: Effects On Fruit Yield and Morphologymentioning
confidence: 88%